Dry Octopus and Marine Worms Processing Business Development in Matwair Village, West Kei Kecil Subdistrict - Daniel Ngabalin; Eygner Gerald Talakua; Frischilla Pentury (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2018)
The purpose of this activity was to establish and develop a processing business for octopus (Octopus sp) and dried sea worms (kian) at Ohoi Matwair. There are two important aspects to starting and developing this business, namely the aspects of production and management. In the aspect of priority production, the problem faced is the drying technique of octopus and traditional sea worms, drying tools and equipment used in processing simple octopus and sea worms, the shape and quality of packaging products for drying octopus and unhygienic sea worms. While the problems related to business management are capital management and production efforts of drying octopus and sea worms that have not been maximized, recording business activities of drying octopus and sea worms has not been done properly, and how to sell or market dried octopus and sea worm products that have not been done well. Through the PRA approach method or participatory rural appraisal as well as three methods in fishery counseling namely lectures, demonstrations and training, the IbM program activities are carried out as a solution to solve the priority problems faced by partners. The amount achieved is 1) Transfer of science and technology from the service team to partners; 2) There has been an increase in partner knowledge about octopus and dry sea worm processing businesses by 38.7%; 3) There are 25 products of octopus and dry sea worms; 4) There are two drying tools used by partners; 5) There are 5 notebooks submitted to partners, but partners are only able to record 2 notebooks (books of purchase and sale); and 6).A total of 25 pieces of octopus and dry sea worms were reached the market in the Ohoi Matwair region.